VOCAL TECHNIQUE TRAINING METHOD TO IMPROVE THE ABILITY TO SING THE SONG BANGUN PEMUDI PEMUDA IN THE STUDENT CHOIR OF STATE SENIOR HIGH SCHOOL 4 SIDOARJO - Saputra, Wimantika Andri; Murbiyantoro, Heri (Solah, 2025)
The song Bangun Pemudi Pemuda was presented by the student choir of SMA Negeri 4 Sidoarjo in order to commemorate the national day. This study aims to describe the training methods applied in improving the vocal abilities of the choir members, as well as to present the results of the implementation of these methods in performing the song Bangun Pemudi Pemuda. The research method used is qualitative, with data collection techniques through observation, interviews, and documentation in the form of photos and video recordings. The data sources in the study consisted of primary data sources obtained directly from the main source, namely Danu Hisa Kumala, M.Pd, then secondary data sources were obtained from students who served as the head of the SMA Negeri 4 Sidoarjo choir team. The training process was carried out directly in the practice room of SMA Negeri 4 Sidoarjo. The training was carried out by implementing several methods, including lectures, demonstrations, drills, and solfeggio. The use of these methods aims to facilitate the process of understanding and mastering vocal techniques, especially in the aspects of breathing, articulation, intonation, and phrasering. The results of the application of this training method show the effectiveness and efficiency in improving the mastery of the Bangun Pemudi Pemuda song material by the choir team.